2016
DOI: 10.1016/j.ijnonlinmec.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical solutions of the Local Inertial Equations

Abstract: Neglecting the convective terms in the Saint-Venant Equations (SVE) in flood hydrodynamic modelling can be done without a loss in accuracy of the simulation results. In this case the Local Inertial Equations (LInE), are obtained. Herein we present two analytical solutions for the Local Inertial Equations. The first is the classical instantaneous Dam-Break Problem and the second a steady state solution over a bump. These solutions are compared with two numerical schemes, namely the first order Roe scheme and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In the same paper, it was given a novel stability condition where both flow depth and velocity were taken into account, but again no theoretical justification was given. In Martins et al (2016a), a Finite Volume scheme based on the Roe Riemann solver and a MacCormack finite difference scheme were tested using the dambreak exact solution. The results showed that numerical algorithms written in conservative form are able to reproduce moving discontinuities arising in LInA, but the treatment of the wetting-drying fronts was not clearly specified.…”
Section: Introductionmentioning
confidence: 99%
“…In the same paper, it was given a novel stability condition where both flow depth and velocity were taken into account, but again no theoretical justification was given. In Martins et al (2016a), a Finite Volume scheme based on the Roe Riemann solver and a MacCormack finite difference scheme were tested using the dambreak exact solution. The results showed that numerical algorithms written in conservative form are able to reproduce moving discontinuities arising in LInA, but the treatment of the wetting-drying fronts was not clearly specified.…”
Section: Introductionmentioning
confidence: 99%
“…In the sequence, they use an operator splitting technique to extend to a two-dimensional case. Martins et al [16] solved the Local Inertial Equations in flood hydrodynamic modeling obtained by neglecting the convective terms in the Saint-Venant equations. According to the authors neglecting these terms do not impair the problem accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors showed that models based on the Locally Inertial Formulation are more robust than the ones based on the full SWE. Locally Inertial Formulation show a similar overall accuracy to SWE, with a significant decrease in computational time (Aronica et al ., ; Bates et al ., ; Neal et al ., ), which is in accordance with recent studies on the analytical solutions for subcritical flows (Martins et al ., , ).…”
Section: Introductionmentioning
confidence: 99%